Study of nutrition in poor children in Lima - Part Two - Guzmán Barrón, Alberto (1954)
Earlier in this volume Aguilar and Caceres studied from the point of view, chemical and biochemical 100 poor children in Lima, 6 to 14 years old. This paper deals with the study of inorganic phosphorus and alkaline phosphatase in the same children, in order to get an idea of ​​deficiency states of vitamin D, calcium and phosphorus. The average number of inorganic phosphorus is mgrs. 4.78%, 8.76 units of alkaline phosphatase Bodansky, both figures are averages considered normal for children ages indicated. In no case has been found by clinical examination or determination of phosphatases signs of rickets, although the food they receive is poor in calcium. This may be because the subjects studied in school almost entirely properly receive the action of the sun, allowing them to synthesize adequate amounts of vitamin D, which will bring a good use of the little calcium in your diet. These results agree with those made by other researchers in tropical regions.